1997
DOI: 10.1523/jneurosci.17-09-03064.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cell Death Induced by the Mitochondrial Toxin 3-Nitropropionic Acid: Acute Excitotoxic Necrosis and Delayed Apoptosis

Abstract: Impaired energy metabolism may play an important role in neuronal cell death after brain ischemia and in late-onset neurodegenerative diseases. Both excitotoxic necrosis and apoptosis have been implicated in cell death induced by metabolic impairment. However, the factors that determine whether cells undergo apoptosis or necrosis are not known. In the present study, metabolic impairment was induced by 3-nitropropionic acid (3-NP), a suicide inhibitor of succinate dehydrogenase. Treatment of cultured rat hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
147
1
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(162 citation statements)
references
References 66 publications
9
147
1
5
Order By: Relevance
“…Studies have shown that the resulting level of ATP suppression following a 3-NP treatment is dose-and timedependent. For example, Pang, et al (1997) reported that application of a concentration of 3-NP (5 mM) reduces the cellular ATP level in cultured rat hippocampal neurons by about 25% at 2 hrs after the 3-NP treatment. In the current study, we intended to use the highest dose allowed without causing rapid cell death to generate maximal suppression of SDH activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the resulting level of ATP suppression following a 3-NP treatment is dose-and timedependent. For example, Pang, et al (1997) reported that application of a concentration of 3-NP (5 mM) reduces the cellular ATP level in cultured rat hippocampal neurons by about 25% at 2 hrs after the 3-NP treatment. In the current study, we intended to use the highest dose allowed without causing rapid cell death to generate maximal suppression of SDH activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have established that 3-NP exposure induces both apoptosis and necrosis in striatal, cortical, and hippocampal cells (Behrens et al, 1995;Pang and Geddes, 1997). The balance between the two types of cell death depends mainly on the severity of ATP depletion (Eguchi et al, 1997;Leist et al, 1997;Ohgoh et al, 2000) which is closely related with the dose and time of exposure to this toxin.…”
Section: Discussionmentioning
confidence: 99%
“…In primary rat neuronal cultures, 3-NP induces a gradual increase in mitochondrial calcium and reactive oxygen species which are prevented in the presence of caspase inhibitors (Lee et al, 2002a). At higher concentrations, 3-NP administration results in a massive elevation of mitochondrial and cytosolic calcium, a decrease in ATP levels, a rapid mitochondrial membrane depolarization, and the activation of calpains (Lee et al, 2002b;Nasr et al, 2003;Pang and Geddes, 1997). Under these conditions, caspase activity is not affected, which is in agreement with cells undergoing death by necrosis (Nasr et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that 3-NP produced a dose dependent selective toxicity to dopamine neurons in mesencephalic culture that could be attenuated by block ade of NMDA receptors (Zeevalk et al, 1995) and that the initial phase of 3-NP poisoning in vivo selectively inhibited the trichloroacetic acid cycle of GABAergic neurons where the trichloroacetic acid cycle of glia re mained uninhibited, as did the trichloroacetic acid cycle associated with the large neuronal pool of glutamate, which includes glutamatergic neurons (Hassel and Son newald, 1995). However, another study reported that MK-801 and the non-NMDA receptor antagonist, 6-cyano-7 -nitroquinoxaline-2,3-dione, could not protect against neuronal death induced by 3-NP in cultured stria tal and cortical neurons and that MK-801 failed to pre vent apoptotic neuronal death induced by 3-NP in rat hippocampal neuronal cultures (Pang and Geddes, 1997). The possible causes for the discrepancy between those studies and ours might be that the previous ones were in vitro experiments in which the cells would have lacked organized glutamatergic input.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we speculated that apoptosis induced by 3-NP in the striatum might be re lated to excitotoxicity, but this has not been clearly elu cidated in vivo. Although MK-801 could not prevent ap optosis induced by 3-NP treatment in a cell culture sys tem (Pang and Geddes, 1997), there is a possibility that 3-NP toxicity in vivo, in an intact system, could involve apoptosis induction by means of excitotoxicity. There fore, the involvement of excitotoxicity and oxidative stress in apoptosis induced by treatment with 3-NP in vivo requires comprehensive elucidation.…”
mentioning
confidence: 94%